2016
DOI: 10.1192/bjpo.bp.115.002394
|View full text |Cite|
|
Sign up to set email alerts
|

A training programme involving automatic self-transcending meditation in late-life depression: preliminary analysis of an ongoing randomised controlled trial - RETRACTED

Abstract: Late-life depression affects 2–6% of seniors aged 60 years and above. Patients are increasingly embracing non-pharmacological therapies, many of which have not been scientifically evaluated. This study aimed to evaluate a category of meditation, automatic self-transcending meditation (ASTM), in alleviating symptoms of depression when augmenting treatment as usual (NCT02149810). The preliminary results of an ongoing single-blind randomised controlled trial comparing a training programme involving ASTM with a wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Psychobiological factors include endocrine, genetic, inflammatory, neural, and cardiovascular processes that bidirectionally interact to affect LLD risk. Intervention research suggests that MBTs (including yoga 299,330,331 , MBSR 332 , tai chi 333,334 , qigong 302 , and meditation 335,336 ) have potential for improving HPA axis regulation 299 and depressive symptoms in older adults with depression 283,300302 as well as in non-depressed older adults 330332,334336 .…”
Section: Resultsmentioning
confidence: 99%
“…Psychobiological factors include endocrine, genetic, inflammatory, neural, and cardiovascular processes that bidirectionally interact to affect LLD risk. Intervention research suggests that MBTs (including yoga 299,330,331 , MBSR 332 , tai chi 333,334 , qigong 302 , and meditation 335,336 ) have potential for improving HPA axis regulation 299 and depressive symptoms in older adults with depression 283,300302 as well as in non-depressed older adults 330332,334336 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, SSM was found to be easy to learn, can be taught to a group, and is scalable. As such, SSM can, therefore, be positioned to be offered as an augmentation therapy to TAU for individuals with LLD and TR-LLD [37, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, participants’ qualitative feedback included remarks stating that SSM is easily learned and can be practiced as part of a daily routine. The observed practical benefits of SSM included relative affordability, the ability to be taught in a group setting, and easy transferal to community/clinical settings [37, 39]. SSM may additionally ameliorate the cognitive impairments associated with LLD and TR-LLD as other transcendental meditation techniques – practiced twice a day, 2 days per week, for 12 weeks (as in the present study) – have shown improvements in this domain [41].…”
Section: Introductionmentioning
confidence: 87%
“…In addition, small-world brain architecture was stronger in long-term Yoga practitioners and meditation practitioners combined (16 of each practice type) compared to fifteen controls who were similar in age, education, exercise, and engagement in cognitive activities [127]. In an experimental study carried out by Vasudev et al, 24 elderly with depression were randomized to practice automatic self-transcending meditation based on mantra repetition (a form of FA) during a 12-week program, and were compared to 23 waitlist controls, with both groups receiving normal treatment for depression [128]. Depression and anxiety improved in meditation practitioners compared to treatment alone.…”
Section: Integration Of Basic and Clinical Research And Contemplatmentioning
confidence: 99%